2005
DOI: 10.1021/cm047931k
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Oxide Formation on Aluminum Nanoparticles by Transition Metal Coating

Abstract: Nanometer-sized aluminum powder was synthesized by thermal decomposition of an alane solution in the presence of a titanium catalyst under an inert atmosphere. The resulting material, formally devoid of an oxide layer, was used to reduce complexes of gold, nickel, palladium, and silver. The reduction process yielded materials that contained the transition metal at a level between 1 and 3 atom % on a metals basis, as determined by inductively coupled plasma atomic emission spectroscopy and energy dispersive spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(80 citation statements)
references
References 19 publications
1
79
0
Order By: Relevance
“…The main challenge in replacing Ag by the much cheaper metals, Cu and Al, is in avoiding their oxidation at ambient conditions, which usually requires rather sophisticated reaction conditions -the use of hydrocarbon solvents, low precursor concentration and inert atmosphere [19,[21][22][23][24][25][26][27]. For example, Al undergoes rapid oxidation in air (~100 picoseconds) with formation of a dense thin amorphous Al 2 O 3 layer (2-6 nm) [28,29] that results in loss of electrical conductivity and makes aluminum inapplicable for conductive ink formulations. Oxidation of Cu NPs is less rapid compared to Al NPs, especially in the presence of an excess of reducing agent, as we reported recently [19,24].…”
Section: Composition Of Metal-based Inks: Re-quirements and Challengesmentioning
confidence: 99%
“…The main challenge in replacing Ag by the much cheaper metals, Cu and Al, is in avoiding their oxidation at ambient conditions, which usually requires rather sophisticated reaction conditions -the use of hydrocarbon solvents, low precursor concentration and inert atmosphere [19,[21][22][23][24][25][26][27]. For example, Al undergoes rapid oxidation in air (~100 picoseconds) with formation of a dense thin amorphous Al 2 O 3 layer (2-6 nm) [28,29] that results in loss of electrical conductivity and makes aluminum inapplicable for conductive ink formulations. Oxidation of Cu NPs is less rapid compared to Al NPs, especially in the presence of an excess of reducing agent, as we reported recently [19,24].…”
Section: Composition Of Metal-based Inks: Re-quirements and Challengesmentioning
confidence: 99%
“…In 2005, Higa and co-workers reported the use of transition metals to inhibit the formation of an oxide layer over the surface of aluminum nanoparticles [50]. They claimed that treatment of aluminum particles with solutions of certain transition metal complexes resulted in the deposition of a uniform coat of the zerovalent transition metal [50].…”
Section: Ii12 Synthesis and Functionalization Of Aluminum Nanopartimentioning
confidence: 99%
“…They claimed that treatment of aluminum particles with solutions of certain transition metal complexes resulted in the deposition of a uniform coat of the zerovalent transition metal [50]. These reactions, which take advantage of the strongly reducing nature of metallic aluminum, may be termed redox transmetalation reactions [51][52][53][54][55].…”
Section: Ii12 Synthesis and Functionalization Of Aluminum Nanopartimentioning
confidence: 99%
“…42,43 These analytes were specifically chosen because they provided a range of particle sizes, compositions, surface chemistries, and reactivities. [44][45][46][47] For example, previous studies have shown that protecting agents including organic ligands 40,[48][49][50][51][52][53][54] and polymer [55][56][57] or metal coatings 44,58,59 enhanced reactivity properties and provided chemical control over structural attributes like particle size and monodispersity. The STXM-XAS results were consistent with earlier spectromicroscopy studies, 26,55,60 and also revealed new differences in the surface and micron-scale speciation of Al nanoparticles.…”
Section: Introductionmentioning
confidence: 99%